Analisis Kesalahan Berbahasa dalam Tataran Fonologi pada Video Youtube Bule Barbie “Ngomong Bahasa Indonesia 24 Jam? Bule Barbie Jadi Bingung” - Diliana, Ekfindar; Mangunsong, Tio Artha Mega (Lembaga Yasin AlSys, 2023)
Social media platforms like YouTube have gained popularity as a means of disseminating linguistic content. When foreigners, like